Inkjet printing of gold nanoparticles onto a biologically relevant matrix to create quantitative test materials for time‐of‐flight secondary ion mass spectrometry. (6th July 2020) - Muramoto, Shin; Bennett, Joe
Abstract : This study describes the use of inkjet printing for the preparation of test materials containing gold nanoparticles (AuNPs) on a biologically relevant matrix and discusses the methods of using time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) for their spatially resolved quantification. Evaluation of test materials containing AuNPs with nominal diameters of (30, 80, 100, and 150) nm deposited onto gelatin with loadings ranging from 34 fg up to 67 000 fg per spot suggests that ToF‐SIMS has the sensitivity and the dynamic range to quantify NP deposits in a biological matrix at toxicologically relevant concentrations, although it was not capable of reliably determining the size of the AuNPs from the intensity data. Regardless, the ability to extract intensity data from individual regions of interest (ROIs) showed that spatially resolved quantification is possible, even when multiple features exist in a single image and in a single depth profile. The argon gas cluster source used for sputtering led to a matrix removal effect where the matrix surrounding the AuNPs became negligible, which may facilitate the preparation of quantitative test materials.